Hit Me, Fred : Recollections of a Sideman - Wesley, Fred (Book collections on Project MUSE., 2002)
"Wesley's distinctive sound reverberates through rap and hip-hop music today. In Hit Me, Fred, he recalls the many musicians whose influence he absorbed, beginning with his grandmother and father - both music teachers - and including mentors in his southern Alabama hometown and members of the Army band. In addition to the skills he developed working with James Brown, George Clinton, Bootsy Collins, and the many talented musicians in their milieu, Wesley describes the evolution of his trombone playing through stints with the Ike and Tina Turner Revue, Hank Ballard, and Count Basie's band. He also recounts his education in the music business, particularly through his work in Los Angeles recording sessions."--Jacket.